Application of integration methods between university information systems and access control systems - ZHANG Yundong (Tongxin xuebao)
An implementation strategy for achieving stable and reliable integration between university business systems and access control systems, aimed at enhancing the stability and reliability of business system permissions being issued to access control controllers through synchronization strategies and technological innovations, thereby better ensuring the synchronization of access control permissions. By analyzing existing problems, a set of low-coupling and high-efficiency solutions are proposed and implemented, effectively improving the phenomenon of desynchronization and mismatch between access control permissions and business system permissions, and enhancing the stability of the application.